The Management of Artificial Intelligence Innovation to Improve Education Quality at SMK Negeri 1 Grati - Linda Puji Astuti; Taufiq Harris; A. Faizin (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The advancement of Artificial Intelligence (AI) technology has become a key catalyst for change in education, including vocational education, which is required to be responsive to the developments of the 4.0 and 5.0 Industrial Revolutions. In the context of Vocational High Schools (SMK), AI has strategic potential to support the improvement of education quality through more adaptive, efficient, and relevant learning in line with the needs of the labor market. However, the utilization of AI that has not been managed in a planned and systematic way may lead to its instant use, which may not have an optimal impact on the quality of learning. This study aims to examine the management of AI innovation in efforts to improve the quality of education at SMK Negeri 1 Grati, identify factors that support and hinder its implementation, and analyze the effectiveness of the innovation management. This research employs a qualitative approach with a case study design. Data collection was conducted through in-depth interviews, observations, and documentation studies involving school principals, teachers, and relevant stakeholders. Data analysis was carried out interactively through data reduction, data presentation, and conclusion drawing, and its validity was tested using source and technique triangulation. The results of this study are expected to provide a comprehensive overview of AI innovation management based on management functions as a strategy for improving vocational education quality, as well as serve as a reference for schools and stakeholders in formulating policies for the targeted, responsible, and sustainable use of AI.